Пусть I(x)=∫eˣ*sin(x)*dx. Применим метод "по частям". Пусть u=eˣ, dv=sin(x)*dx, тогда I(x)=u*v-∫v*du. Но du=eˣ*dx, v=∫sin(x)*dx=-cos(x). I(x)=-eˣ*cos(x)+∫eˣ*cos(x)*dx. Пусть теперь I1(x)=∫eˣ*cos(x)*dx. Снова применяем метод "по частям", полагая u=eˣ, dv=cos(x)*dx. Тогда du=eˣ*dx, v=∫cos(x)*dx=sin(x) и I1(x)=eˣ*sin(x)-∫eˣ*sin(x)*dx=eˣ*sin(x)-I(x). Мы получили уравнение: I(x)=-eˣ*cos(x)+eˣ*sin(x)-I(x), или 2*I(x)=eˣ*sin(x)-eˣ*cos(x)=eˣ*[sin(x)-cos(x)]. Отсюда I(x)=eˣ*[sin(x)-cos(x)]/2. ответ: eˣ*[sin(x)-cos(x)]/2.
5х-2(х-3)=6х
5х-2х+6=6х
5х-2х-6х=-6
-3х=-6
х=2
----------------------
6х-(2х-5)=2(3х-6)
6х-2х+5х=6х-12
6х-2х+5х-6х=-12
3х=-12
х=-4
-----------------------
х*(х+5)=(х+3)^2
x^2+5x=x^2+6x+9
x^2+5x-x^2-6x=9
-x=9
x=-9